Implementation Of Inside Outside Circle Game To Develop Speaking Skill For The First Grade Of SMAN 1 Toroh In 2012/ 2013 Academic Year - Rahmawati, Diah Fitria, Drs. Djoko Srijono, M. Hum, Drs. Agus Wijayanto MA, Ph. D. (2013)
This research aims to know the implementation of inside outside circle game in improving the students' speaking skill, to know the effect of implementation of inside outside circle game in teaching speaking skill, and to know the students' response in the implementation of inside outside circle game. This research was implemented in SMAN 1 Toroh at the first grade especially in X B in 2012/ 2013 academic year. This research used collaborative research. The method of collecting data were observation, interview, and document. In this method, the collaborator or the teacher helped the researcher in arranging the lesson plan. The collaborator also helped the researcher to solve the problem faced of the students during the implementation this research. The result of this research showed that the implementation of inside outside circle game could improve the studens' speaking skill. It could be seen from the result of pre-test and post-test of the students. The mean score of pre-test of the students was 61,3 (fair) and post-test 74,9 (significant) and the prove result of the implementation was 13,6. Most of the students said that they were interested with the technique. The students could easily learn English speaking. The students also felt confident and bravery to speak English in front of the class or with other friends in the class.